Pengaruh Model Pembelajaran Cooperative Script terhadap Hasil Belajar Siswa di Madrasah Tsanawiyah Al-Istiqamahigobula - Marwatul ummah; Rosita Tabaika; Fitriyah Karmila (Al-Nafis: Jurnal Biologi dan Pendidikan Biologi, 2022)
Education plays an important role in building a country. The better the education in a country, the more developed the country will be. This is because good education will create good Human Resources (HR), and good Human Resources (HR) will certainly be more optimal in developing and advancing the country. Regarding the importance of education for a citizen in an effort to realize a virtuous nation's civilization, the Indonesian government provides a concrete formulation of national education goals. The learning outcomes are not only in the form of mastery of knowledge, but also skills and skills in seeing, analyzing and solving problems, making plans and making distributions. work, thus the activities and products resulting from these learning activities get an assessment. Assessment is not only done in writing, but also orally and performance appraisal. This study aims to analyze the effect of the cooperative script learning model on student learning outcomes at Madrasah Tsanawiyah Al-Istiqamah Igobula.The type of research used in this study was quasi-experimental The design used in this study was the Two group pretest-posttest design. In this design, two groups were selected, then given a pretest to find out early whether there were differences between the experimental groups. and control group. The experimental group is the group that is treated with the Cooperative Script learning model and the control group is the group that is not treated with the conventional learning model. The results of student activities during the learning process are quite good, as well as the activities of a researcher who is observed by the teacher in question is in accordance with the lesson plan that has been set. Based on the results of the analysis carried out with the t test, the t value obtained = 1.733 at a significant level of 0.05 which states that the alternative hypothesis (Ha) is accepted. This means that there is a significant influence between the influence of the Cooperative Script learning model on the learning outcomes of students at Madrasah Tsanawiyah Al-Istiqamah Igobula. Keywords: Cooperative script learning ourcome